Democratic Policy Implementation in an Ambiguous World. - Fowler, Luke. (Albany : State University of New York Press, 2023)
Explains the complexities of policy implementation and why attempts to translate new laws into effective and enduring policy sometimes succeed and sometimes fail.
Summative Points on Policy Implementation -- Implications for Theory -- Empirical Challenges and Future Research -- Implications for Democratic Governance -- Appendix -- Methods Memo for Chapter 3 -- Methods Memo for Chapter 4 -- Methods Memo for Chapter 5 -- Methods Memo for Chapter 6 -- References -- Index
JSTOR
Keywords: Policy sciences; Political planning; Decision making; Sciences de la politique; Politique publique; Prise de décision.; decision making; POLITICAL SCIENCE / Public Policy / General; Decision making; Policy sciences; Political planning